As práticas escolares a partir do jornal Mundo jovem, 1978-1988 - Marin, Diosen (2020)
This text presents the mediation of Mundo Jovem newspaper on school practices, during the final years of the Brazilian Civic-military Dictatorship (1978-1988). It aims to answer the following question: how the school practices on primary education of public schools in the state of Rio Grande do Sul are mediated by the catholic printed material, published between 1978 and 1988? To answer this and other questions that emerged from the research, the following goals were constituted: 1) identify how the military government intended to legitimate their decisions by Public Policies on the educational field between 1978 and 1988; 2) verify the actions of the Catholic Church by official documents about its comprehension of means of communication 3) define the concept of education by the publications of the newspaper entitled Mundo Jovem; 4) examine the presence of publication that intended to guide teachers‟ schools' practices on Mundo Jovem newspaper; 5) develop a methodological path, aiming to analyze by Mundo Jovem newspaper and semi-structured interviews, the school practices. In this regard, the applied methodology to carry on this research is a methodological path composed of two distinct phases. Firstly, the Content Analysis proposed by Bardin (2004) was used. Secondly, considering as base the categories established by the newspaper‟s analysis, semi-structured interviews were conducted with teachers and students that used this printed mean as support to their school practice. It was concluded that is necessary to promote circularity of information and not only analyze what is proposed in the publication because by conducting this research by analyzing the newspaper or the interviews it was possible to identify Mundo Jovem Newspaper mediating school practices.